Current Therapy and Therapeutic Targets for Microsporidiosis - Wei, Junhong; Fei, Zhihui; Pan, Guoqing; Weiss, Louis M.; Zhou, Zeyang (Frontiers in Microbiology, 2022)
Microsporidia are obligate intracellular, spore-forming parasitic fungi which are grouped with the Cryptomycota. They are both opportunistic pathogens in humans and emerging veterinary pathogens. In humans, they cause chronic diarrhea in immune-compromised patients and infection is associated with increased mortality. Besides their role in pébrine in sericulture, which was described in 1865, the prevalence and severity of microsporidiosis in beekeeping and aquaculture has increased markedly in recent decades. Therapy for these pathogens in medicine, veterinary, and agriculture has become a recent focus of attention. Currently, there are only a few commercially available antimicrosporidial drugs. New therapeutic agents are needed for these infections and this is an active area of investigation. In this article we provide a comprehensive summary of the current as well as several promising new agents for the treatment of microsporidiosis including: albendazole, fumagillin, nikkomycin, orlistat, synthetic polyamines, and quinolones. Therapeutic targets which could be utilized for the design of new drugs are also discussed including: tubulin, type 2 methionine aminopeptidase, polyamines, chitin synthases, topoisomerase IV, triosephosphate isomerase, and lipase. We also summarize reports on the utility of complementary and alternative medicine strategies including herbal extracts, propolis, and probiotics. This review should help facilitate drug development for combating microsporidiosis.